Diagnosis and differentiation of pathological concentric left ventricular hypertrophy - Millisani, Hayla Iqda; Karolina, Wella (Heart Science Journal, 2025)
Identifying the diagnosis and differentiation of concentric left ventricular hypertrophy (LVH) can be crucial, as the various etiology ofter similar characteristics and morphology. Concentric left ventricular hypertrophy (LVH) is the term used to describe the enlargement of the left ventricle (LV), the increase in the mass and thickness of the LV wall which can occur in response to pressure overload. The most common etiology of concentric hypertrophy include the systemic hypertension, aortic stenosis and hypertrophic cardiomyopathy (associated with sarcomere mutations, infiltrative cardiac diseases, and storage disorders). Cardiac imaging is the predominant modality for visualizing and quantifying LVH in clinical practice and often collaborates with an established diagnosis. Echocardiography, the primary imaging modality, enables a thorough evaluation of left ventricular systolic and diastolic function. Cardiovascular magnetic resonance offers further benefits by correctly measuring left ventricular and right ventricular sizes and mass, as well as characterizing myocardial tissue properties. These measurements can provide valuable insights for making a final diagnosis.